Risky sexual behavior and porn in a population of adult people in Peru - Iglesias-Osores, Sebastian (2023)
Objective: The aim of this study is to identify the relationship between pornography consumption and risk behaviors. Material and Methods: Sexual risk behaviors and pornography consumption were assessed. Snowball sampling had 245 participants, who agreed to participate voluntarily. Data were collected using a Google Forms questionnaire. Participants gave their informed consent after reading the description of the study, where the anonymity of the survey was indicated. Results: For the odds ratio analysis it was found that the highest odds of being HIV positive were associated with being LGBT, with not having the perception of pornography encouraging condomless sex. Individuals who consume pornography were associated with being LGBT and with not having the perception that the type of pornography they view influences their relationships. Higher odds of having had anal sex without a condom were associated with being LGBT, having a higher education, having a monthly salary higher than minimum wage, and having group sex. Future research is needed to further study the effects of pornography on the sex lives of those who consume it. Conclusion: LGBT participants were found to be at higher risk for HIV, condom non-use, pornography viewing, and casual sex. STIs were associated with higher education and having a steady partner.